E-cadherin endocytosis promotes non-canonical EGFR:STAT signalling to induce cell death and inhibit heterochromatinisation. - Miguel Ramirez Moreno; Amy Quinton; Eleanor Jacobsen; Przemyslaw A Stempor; Martin P Zeidler; Natalia A Bulgakova (PLoS Genetics)
Signalling molecules often contribute to several downstream pathways that produce distinct transcriptional outputs and cellular phenotypes. One of the major unanswered questions in cell biology is how multiple activities of signalling molecules are coordinated in space and time in vivo. Here, we focus on the Signal Transducer and Activator of Transcription (STAT) protein as a paradigm of signalling molecules involved in several independent signalling pathways. Using Drosophila wing discs as an in vivo model, we demonstrate an interplay of at least three STAT activities in this tissue. In addition to the 'canonical' pathways, in which STAT is phosphorylated and activated by Janus Kinases, STAT is involved in two 'non-canonical' pathways. In one pathway, STAT is activated by the Epidermal Growth Factor Receptor (EGFR), promoting apoptosis. In the other, it binds the Heterochromatin Protein 1 (HP1) to enhance heterochromatin formation. We provide evidence that while the 'canonical' STAT signalling is dominant over 'non-canonical' pathways, EGFR:STAT and HP1:STAT pathways compete for the availability of unphosphorylated STAT. We also describe a central role for the cell-cell adhesion protein E-cadherin, with both EGFR and STAT colocalising with E-cadherin at cell-cell junctions and on intracellular vesicles. We show that elevated intracellular E-cadherin promotes EGFR:STAT pathway leading to apoptosis, which is prevented by inhibiting E-cad endocytosis. Taken together, we conclude that E-cadherin controls the balance between two non-canonical STAT activities. We hypothesise that this balance represents a tumour-suppressive mechanism, in which junctional disassembly in dysregulated epithelial-to-mesenchymal transitions would shift this balance towards the EGFR:STAT signalling to promote apoptosis.